Estudos hidrológicos aplicados para avaliação de secas na Bacia Hidrográfica do Rio Meia Ponte - Melo, Denise Christina de Rezende (2024)
The objective of this study was to verify the influence of land use, water use, and climate change, with alterations in precipitation on minimum flows, over time, and to assess droughts, in the Meia Ponte River Watershed. Hydrological data from stations located in the basin, pertaining to the National Hydrometeorological Network and the National Institute of Meteorology (INMET), were used. For the analysis of minimum flows, a physical and socioeconomic characterization of the basin was conducted, along with statistical analyses and flow simulations using the HYMOD hydrological model. In the drought assessment, three drought indices were utilized: Standardized Precipitation Index (SPI), Standardized Streamflow Index (SSI), and Standardized PrecipitationEvapotranspiration Index (SPEI). The results indicated significant changes in land use in the Meia Ponte River Watershed over time, primarily due to the increase in urbanized areas and areas with irrigated agriculture. In addition to reduced precipitation and increased temperatures, this set of factors may have contributed to the decline in minimum flows in the basin over the years. The statistical analyses applied to flows and precipitation showed that most of the stations are non-stationary, non-homogeneous, and dependent, likely due to these anthropogenic changes. Modeling allowed for the estimation of flows for the last 20 years, with observed flows falling below the simulated flows, particularly from 2015 to 2021, when daily values remained below the reference flows Q95 and Q7,10. The drought assessment using drought indices and simulated flows with the hydrological model identified the driest years in the historical series, revealing periods of meteorological, hydrological, agricultural, and even socioeconomic droughts